PENGUATAN BRAND DAN REPOSITIONING UMKM MASYARAKAT DESA BEDALI - Moh. Irmawan Jauhari; Ammar Kukuh Wicaksono; Wafiq Nurfiani Pradita (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2025)
This activity aims to introduce and develop UMKM in Bedali Village, Ngancar, Kediri. The method used is ABCD considering that the Bedali community already has assets and potential that can be maximized and has the opportunity to be sustainable after the service is carried out. ABCD has urgent steps, namely Discovery, Dream, Design, Define, and Destiny. The result is an activity to strengthen UMKM in Bedali Village with a pilot project of Bu Aminah chips, Pineapple Juice (GEGE) & Jamu Sinom (GEGE), and Lapis Kukus Tugu Kediri resulting in two main points so that UMKM become strong and empowered. First, expanding the product promotion area so that the UMKM product is known by more people and has a wider marketing area. Second, market expansion can be done by participating in certain events both locally and regionally.